Digital information and communication technologies ( ICT ) in Social Service graduations in the State of Paraná - Schuartz, Antonio Sandro (2020)
This article presents the results of the exploratory and descriptive study that had among its objectives: a) to identify the number of graduations offered in Social Work in the State of Paraná; b) recognize whether there are disciplines related to teaching about ICT among the curricular matrices of the courses; c) reflect on the possibilities and limits of the ICT in the scope of Social Work. The first approximation with the question came from the material available online. The study pointed out that more than 20 years have passed since the promulgation of the Curricular Guidelines for Social Work courses, when it was already established that among the skills to be achieved by future social workers in training was to master computer resources. Currently, however, less than 20% of the graduations offered in the State of Paraná have this theme in their curricular matrices.